PROPERTY OF SPOUSES AND FORMER SPOUSES (LEGAL REGULATION) (Conferencea, 2022)
This article is devoted to the disclosure of the essence of the legal order of the property of spouses and former spouses. The study is aimed at shedding light on the fact that the property rights of spouses are a complex legal category, as well as revealing the interdependence of civil law, family law and business law, corporate rights. The article puts forward proposals for the development of the theory and practice of regulating the property rights of spouses and former spouses.